John Scottus Eriugena - Carabine, Deirdre (Great medieval thinkers., 2000)
This is an introduction to the 9th-century philosopher and theologian John Scottus Eriugena, perhaps the most important philosophical thinker in Latin Christendom in the period between Augustine and Anselm. Eriugena was known as the interpreter of Greek thought to the Latin West.